2013
DOI: 10.1159/000346831
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Recurrent Breast Cancer Showing Long-Term Survival after Developing Pericardial Effusion and Cardiac Tamponade Caused by Carcinomatous Pericarditis

Abstract: Background: Malignant pericardial effusion caused by carcinomatous pericarditis is a complication of advanced malignancy. Breast cancer is the second most important cause of malignant pericardial effusion. Malignant pericardial effusion is the end stage of breast cancer, and the prognosis is very poor. Pericardial effusion may cause cardiac tamponade and sudden death if it is not controlled properly. There is a debate on which is the best method to control pericardial effusion. Case Report: We describe the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Interestingly, the patient had survived for about 5 years since first diagnosis with a pericardial metastasis and received many lines of chemotherapy following paclitaxel treatment, including docetaxel. No pericardial effusion was found during the rest of the treatment, 11 as also shown by our case. Furthermore, Einama et al observed that the time taken for paclitaxel to disappear in the pericardial effusion was shorter than for that in the plasma.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, the patient had survived for about 5 years since first diagnosis with a pericardial metastasis and received many lines of chemotherapy following paclitaxel treatment, including docetaxel. No pericardial effusion was found during the rest of the treatment, 11 as also shown by our case. Furthermore, Einama et al observed that the time taken for paclitaxel to disappear in the pericardial effusion was shorter than for that in the plasma.…”
Section: Discussionsupporting
confidence: 88%
“…Taxane‐based chemotherapy is among the most effective palliative treatment for MBC. Previously, two reports have shown a good efficacy of single weekly paclitaxel therapy to relieve malignant pericardial effusions and cardiac tamponade in patients with MBC 11,12 . Ikeda et al reported it as a second‐line regimen upon relapse of the cardiac tamponade after an anthracyclin‐based treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with available literature, adequate treatment of MPE almost invariably prevents death, and, in suitable patients, affords the administration of systemic treatments. In chemo-sensitive diseases, this can translate into a long life expectancy 30 , 31 : we had 7 patients surviving 1 year or more. Moreover, in patients with HER2 positive breast cancer and in lung cancer patients with EGFR mutation positive disease, targeted treatment may potentially obtain even better results.…”
Section: Discussionmentioning
confidence: 99%
“…CT as the initial manifestation of primary malignant tumours with no pericardial origin such as lung, urinary bladder, kidney, vagina, ovarian, fallopian tube, endometrium, uterine cervix, colon, stomach, thyroid, thymus, breast, lymphoma, and melanoma have all been reported [[25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39]]. Furthermore, sudden death due to CT caused by metastatic lung cancer has been mentioned [40,41].…”
Section: Discussionmentioning
confidence: 99%